Dirāsah Taqyīmīyah ‘alá Barāmij al-Qaryah al-‘Arabīyah fī Qism Ta‘līm al-Lughah al-‘Arabīyah bi-Jāmi‘at Jākartā al-Ḥukūmīyah - Syamsi Setiadi; Ahlan Faruqi (Universitas Negeri Jakarta, 2019)
The purpose of this study was to evaluate the 3rd Qaryah ‘Arabīyah (QA) program carried out by the Arabic Language Education Study Program, Universitas Negeri Jakarta. This QA activity has been carried out for 3 years ago. The method used in this study is program evaluation using the CIPP model which consists of 4 component elements, namely Context, Input, Process, and Product. The results of the study show the following: (1) Context evaluation got a value of 73.6%, indicating that the context evaluation was in a Good category; (2) Evaluation of input scores 68.7%, these results indicate that evaluation of inputs is in a Good category; (3). Process evaluation gets a value of 67.7%, which indicates that the Evaluation Process is in a Good category; 4) Product evaluation gets a value of 73.7%, which indicates that the product evaluation is in a Good category. Based on the calculation of the interpretation of the four components, a result of 74.4% was found for the evaluation of the QA, these results indicate that the implementation of the 3rd QA is in the category of Good. The results of the study indicate that the QA program is a program that is useful for increasing students' learning motivation and Arabic language competence because of the creation of a good Arabic speaking environment.